Modern conditions for ensuring competencies and learning outcomes by distance learning - Riabchykov , M.; Riabchykova, O. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to the problem of determining the most effective methods and techniques of distance learning to provide the basic descriptors in terms of the competence approach, taking into account the necessary components of the learning process. It is shown that distance education creates a real basis for the democratization of the education process, real educational mobility, and creation of intercultural educational programs. Insufficient development of research in the field of distance education in Ukraine has been identified. The general problem is to prove the possibility of providing the necessary competencies by distance learning methods, while it is necessary to define the concept of competencies as objectively as possible, to identify the main factors influencing them, to introduce distance education methods that improve the learning process. During considering distance education, the problem of competence formation was insufficiently covered. Competence is considered as a system of descriptors. Building directions of acquisition of descriptors related to communication, the ability to self-learning necessarily accompanies distance learning. The modern means and processes of distance education, which implement organizationalmotivational, organizational-substantive, control-regulating, operational-activity, evaluation-effective components, are considered. The organization of the teacher's workplace that implements the real procedural component of training is substantiated. To implement a comprehensive system of verbal and nonverbal methods, it is desirable to use a second computer in conjunction with a specially mounted video camera, a third computer for operational testing, a large screen or projector to attract a large number of participants. To identify the impact of the provided distance learning methods on the formation of competencies, surveys of outsiders, students and schoolchildren on the formation of descriptors were conducted. Studies have shown the stability or improvement of the main descriptors. The organization of training with the organization of training project groups allows achieving an increase in results for all descriptors.